Mrs. Lane is a pain! - Gutman, Dan (Gutman, Dan. My weirder school, 2014)
"It's time for the annual Ella Mentry School talent show, and this year Principal Klutz has hired a wacky professional, Mrs. Lane, to help the kids with their talents"--